The Microstructure and Mechanical Properties of As-cast Mg-10Gd-3Y-xZn-0.6Zr (x = 0, 0.5, 1 and 2 wt%) Alloys - Ding,Zhibing (2018)
The microstructure, mechanical properties and fracture behavior of as-cast Mg-10Gd-3Y-xZn-0.6Zr (x = 0, 0.5, 1 and 2 wt%) alloys have been investigated by X-ray diffraction (XRD), optical microscopy (OM), scanning electron microscopy (SEM) and tensile tests. The experimental results reveal that the microstructure of the alloy without Zn contains α-Mg and Mg24(Gd,Y)5 phase, the microstructure of the alloy with 0.5% Zn contained of α-Mg, (Mg,Zn)3(Gd,Y) and Mg24(Gd,Y,Zn)5 phase, whereas when Zn content was 1% and 2%, the Mg12(Gd,Y)Zn phase and some needle-shaped stacking faults notably appear and the Mg24(Gd,Y,Zn)5 phases completely disappear. Moreover, a new 18R long period stacking ordered (LPSO) phase is observed in grain boundaries with increasing Zn content up to 2%. The tensile tests indicate that the alloy containing 0.5% Zn shows the optimal mechanical properties and the ultimate tensile strength (UTS), yield strength (YS) and elongation are 228MPa, 172MPa and 5.1%, respectively. As indicated by fracture analyses, the fracture modes of the alloys with 0%, 1% and 2% Zn are brittleness transcrystalline fracture, and the tensile fracture mode of 0.5% Zn alloy is typical tough transgranular fracture.